Linguistic Variation and Scribal Practice in Medieval Iceland: A study of five 14th-century manuscripts - Johnstone, Claire Christina, 1985- (2010)
When looking at Icelandic manuscripts from the 14th-century, it is obvious that the Icelandic language was in a period of extensive change. This study will examine a handful of those changes in an attempt to establish possible conclusions about the mechanisms of language change in Iceland and how it spread. The best and easiest way to go about doing this would be to compare copies of manuscripts to their exemplar in order to see exactly how and where the changes take place. However, because so few of the early manuscripts remain, this is simply not possible with 14th century scripts. Instead, the focal point of such a study falls on the scribes. Because they are, in a sense, the recorders of language, a scribe’s work can reflect the grammatical and linguistic conventions of his time. Thus, by examining the register of one scribe over several manuscripts containing several texts of varying age and origin it might be possible to separate the scribe’s own language from that of his exemplar. To achieve this end, it is important to consider consistency; dominant characteristics of language vary from manuscript to manuscript and the frequency of the occurrence of a particular change or archaism might indicate how established that feature is in the language of the scribe. For instance, if the scribe uses a linguistic element, old or new, 100 percent of the time, it can be argued that the feature is consistent with both the scribe’s language and that of his exemplar. That being said, some caution must be exercised when making such assertions. In the case of 14th century Icelandic, a standardized orthography had not yet been established in the same way modern orthography has, meaning certain inconsistencies are natural and 6 can be expected. It is therefore important to identify which are normal and which are products of linguistic change. From there, an investigation into the causes of such deviations with the consideration of scribal practice helps to determine the stage of development and the nature of linguistic ...